Temperature effects on the growth and survival of tdh positive Vibrio parahaemolyticus in tissues of postharvest Manila clam (Ruditapes philippinarum). (October 2018) - Lopez-Joven, Carmen; de Blas, Ignacio; Roque, Ana
Abstract: Bivalve storage at inadequate temperatures contains greater densities of Vibrio parahaemolyticus . The objective of the present study was to determine if there were any differences in growth and survival of potentially pathogenic V. parahaemolyticus ( tdh positive) in relation to nonpathogenic V. parahaemolyticus ( tdh-trh negative) levels in Manila clams ( Ruditapes philippinarum ) when exposed to different postharvest temperatures. Clams were depurated then exposed to known doses of both potential pathogenic and nonpathogenic V. parahaemolyticus for 24 h. Clams were then kept at the following temperatures corresponding to the Mediterranean summer (28 °C), winter (15 °C) and refrigeration (4 °C) for 96 h. Vibrio parahaemolyticus densities were determined at 0, 24, 48, 72 and 96 h of postharvest storage. Both isolates of V. parahaemolyticus multiplied rapidly in live clams held at 28 °C, (increase of 3 logs CFU/g at 72 h). Nonpathogenic V. parahaemolyticus in clams stored at 4 °C and 15 °C showed 1 log CFU/g and 2 log CFU/g decrease at 96 h, respectively, while no significant differences were detected for pathogenic V. parahaemolyticus at these temperatures after 96 h. Highlights: Vibrio parahaemolyticus levels in clams at different temperatures were provided. Potentially pathogenic and nonpathogenic V. parahaemolyticus were compared. tdh-trh negative V. parahaemolyticus stored at 4 °C and 15 °C showed decrease at 96 h. Levels of tdh positive V. parahaemolyticus in clams at 4 and 15 °C are maintained.